Determinants of Income and Profitability in Smallholder Seaweed Farming and Their Implications for Rural Livelihoods in Indonesia - Saville, Ramadhona; Nafysa, Enza; Hatanaka, Katsumori; Shimoguchi, Nina N.; Pratiwi, Chairani P. (AGRARIS: Journal of Agribusiness and Rural Development Research, 2025)
The rural population in Indonesia, heavily reliant on agriculture and fishery, constitutes approximately 60% of the nation's population. Seaweed cultivation has emerged as a significant economic activity among coastal communities, particularly in Seriwe Village, West Nusa Tenggara Province. Despite its significance, studies detailing financial viability and profitability in rural-level seaweed farming remain scarce, limiting effective management and targeted policy interventions. This study assessed the profitability and business feasibility of seaweed cultivation and identified factors influencing the income of seaweed farmers in the village. Utilizing multiple regression analysis, we standardized variable data and evaluated factors such as gender, experience, age, education, cultivation area, seed price, selling price, labor, and capital investment. Data collection involved interviews with 50 seaweed farmers and five middlemen, focusing on sociodemographic profiles, variable and fixed costs, and revenue. The Revenue Cost Ratio of 1.84 confirms the economic viability of seaweed farming, demonstrating substantial profitability in Seriwe Village. The multiple regression analysis results, with an adjusted R-squared value of 0.985, indicated that the cultivation area, capital investment, and selling price significantly influence farmers' income (p < 0.001). Gender and age also played a significant role (p < 0.05). Practical strategies to increase seaweed farmers’ income include forming farmers' groups and cleaning the harvested seaweed. Understanding these factors is crucial for implementing effective interventions and policies to support seaweed farmers. This study highlights the importance of targeted support, such as training programs, to empower farmers and enhance the economic resilience of coastal communities.